Validation of the Core Seven-Emotions Inventory – short form - Cheong, Moon Joo (Integr Med Res, 2019)
BACKGROUND: This study aimed to evaluate the reliability and validity of short form of the Core Seven Emotions Inventory (CSEI-s) scale. METHODS: The participants were third-grade Korean Medicine University students As with the original CSEI, the scales in the short form (CSEI-s) were composed of seven factors and consisted of 28 items in total. The internal consistency coefficient was calculated, and a confirmatory factor analysis was conducted to verify the reliability of the short form scale. Finally, to verify the validity of the abbreviated scale, a correlation analysis with the abbreviated scale and the CSEI-s scale was conducted. RESULTS: A 178 among 200 initial participants were included in the analysis (mean age: 24.5 years). The results of the exploratory factor analysis made from the 28 items of the seven factors of the CSEI-s showed that the factor loadings were as high as 0.64–0.89, excluding the tenth item of fear (0.52), and the model fit also had a good confirmatory factor with the analysis result. The results of the reliability verification showed that the Cronbach α values of all seven subscales of the short-form CSEI scale were 0.7 or higher, and the overall reliability was 0.83. A factor analysis revealed that the factor loadings were adequate, and their reliability and validity were confirmed for the CSEI-s scale, making it applicable to measuring the core seven emotions of patients in clinical practice. CONCLUSION: CSEI-s scale may apply to measure core emotions of the patient in a clinical setting.